2016
DOI: 10.5005/jp-journals-10005-1360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of the Antibacterial Activity againstStreptococcus mutansof Grape Seed Extract at Different Concentrations with Chlorhexidine Gluconate: Anin vitroStudy

Abstract: IntroductionStreptococcus mutans has been implicated as primary microorganisms which cause dental caries in humans. There has been an increased interest in the therapeutic properties of some medicinal plants and natural compounds which have demonstrated antibacterial activities. Grape is one of the plants of this group which contains tannin and polyphenolic compound.AimTo evaluate and compare antibacterial activity of grape seed extract at different concentrations with chlorhexidine gluconate against S. mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 93 publications
1
27
1
3
Order By: Relevance
“…Particularly in the case of S. mutans, studies reviewed give support to the idea that dental GSE treatment may inhibit biofilm formation and bacterial colonization in the dental environment (Furiga et al, 2009(Furiga et al, , 2014Swadas et al, 2016;Thimothe et al, 2007;Zhao et al, 2014). Of the five studies cited, three found significant inhibition of S. mutans biofilm formation in single strain (Singla et al, 2018;Zhao et al, 2014) and multiorganism (Furiga et al, 2014) conditions by GSE.…”
Section: Bacterial Inhibition By Gsementioning
confidence: 89%
“…Particularly in the case of S. mutans, studies reviewed give support to the idea that dental GSE treatment may inhibit biofilm formation and bacterial colonization in the dental environment (Furiga et al, 2009(Furiga et al, , 2014Swadas et al, 2016;Thimothe et al, 2007;Zhao et al, 2014). Of the five studies cited, three found significant inhibition of S. mutans biofilm formation in single strain (Singla et al, 2018;Zhao et al, 2014) and multiorganism (Furiga et al, 2014) conditions by GSE.…”
Section: Bacterial Inhibition By Gsementioning
confidence: 89%
“…En los países latinoamericanos pertenecientes al área andina como el Ecuador, se presentan una variedad de plantas, cuya estructura cuenta con diferentes aceites esenciales y polifenoles (19) que incitan a buscar a partir de extractos vegetales y fuentes naturales de fácil acceso, a elementos antioxidantes con propiedades biológicas y antibacterianas (16) , sin efectos colaterales, que consigan actuar sobre cepas de microrganismos responsables de diferentes enfermedades (20) .…”
Section: Discussionunclassified
“…La uva se muestra como un fruto de uso frecuente yfácil obtención, sin embargo cuando se trata de obtener extractos a partir de ella, nos encontramos ante una gran variedad de técnicas (19) , lo cual dificulta la obtención de un resultado conclusivo (18) , la técnica de obtención de extracto empleada en este estudio si bien es aceptada, desencadena resultados que merecen ser probados ejecutando otras técnicas de obtención (20) , sin embargo, los resultados demostraron que los extractos de semilla al 100% cuentan con una actividad elevada que podría explicarse por la capacidad de antioxidantes relacionada al contenido de polifenoles totales (21) .…”
Section: Discussionunclassified
“…[14,15] Grape Seed extract (GSE) is one of the natural products that was found to be rich in polyphenolic compounds such as epicatechin and proanthocyanidins which are known for their antibacterial effect. [16] This study was, thus, conducted to compare the antibacterial effects of diode laser and GSE to CHX and investigate the effects of using them as cavity disinfectants on bond strength of glass ionomer restorations to dentine in primary teeth. In the present work, the null hypotheses tested were (1) no difference existed in antibacterial activity against Streptococcus mutans (S.mutans) between diode laser, GSE and CHX and (2) the tested cavity disinfectants had no effect on shear bond strength of glass ionomer to dentin in primary teeth.…”
Section: Introductionmentioning
confidence: 99%